2016
DOI: 10.2741/e767
|View full text |Cite
|
Sign up to set email alerts
|

BRIP1 a potential candidate gene in development of non-BRCA1 2 breast cancer

Abstract: BRIP1 encodes a protein belonging to the RecQ DEAH helicase family. It interacts with BRCA1, and is involved in the repair of DNA damage and tumor suppression. Aberrations in BRIP1 have been mainly associated with the development of breast cancer (BC), ovarian cancer, and type J Fanconi anemia. Based on recent work, we hypothesize that BRIP1 might be the gene involved in the onset of BC in families that do not show BRACA1/2 mutations. This review will focus on the findings supporting this hypothesis, the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…36,37 It was also predicted that BRIP1 gene may be susceptible to breast, prostate and ovarian cancer. 21,36,38 Other studies found that the presence of the SNPs in BRIP1 gene has association with the commencement of prostate cancer. 39,40 In this present study, BRIP1 gene was observed as highly expressed in BC patients compared to healthy people which has similarities with the findings of other study.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 It was also predicted that BRIP1 gene may be susceptible to breast, prostate and ovarian cancer. 21,36,38 Other studies found that the presence of the SNPs in BRIP1 gene has association with the commencement of prostate cancer. 39,40 In this present study, BRIP1 gene was observed as highly expressed in BC patients compared to healthy people which has similarities with the findings of other study.…”
Section: Discussionmentioning
confidence: 99%
“…Our microarray analysis clearly shows that the BRIP1, FANCB, and FANCM genes, which are part of the FA pathway, are specifically upregulated in CTC-MCC-41 cells, suggesting that metastases-competent colon CTCs require the FA pathway for survival in vivo in the bloodstream and efficient growth in distant organs. BRIP1 alterations have been associated with the development of ovarian and breast cancers (33 ). However, the real function of FA pathway proteins in colon CTCs is not known yet.…”
Section: Discussionmentioning
confidence: 99%
“…BRIP1 is a member of the RecQ DEAH helicase family, and is encoded by BRIP1, a tumor suppressor gene involved in the DNA repair pathway, via its interaction with BRCA1 (Ouhtit et al, 2016). In Levitus et al (2004) reported 2 new genetic subtypes excluded from 9 known subtypes (A, B, C, D1, D2, E, F, G, and L), including FA-J, based on 8 unrelated FA patients, and defined FA-J cell line with monoubiquitinated FANCD2, which complemented group FA-I but did not complement each other, indicating a downstream defect in FA-J cells (EUFA1289 cells).…”
Section: Brip1/fancjmentioning
confidence: 99%